Avalanche feeding of the Djankuat Glacier - V. V. Popovnin; T. V. Pylayeva (Лëд и снег, 2015)
In order to evaluate the contribution of snow avalanches, coming from outside the glacier limits, into the seasonal accumulation, an original algorithm is proposed for glaciers with ongoing terrestrial mass balance programme. It was tested on the Djankuat Glacier, Caucasus. A case study was realized for 1998/99 balance year when accumulation value was the closest to its long-term mean over the 46-year-long monitoring period. Snow avalanche feeding turned out to be only 2.8 per cent of total accumulation that is about an order of magnitude smaller than assumed hitherto.